ANALISIS KESULITAN MENYELESAIKAN SOAL MATEMATIKA MATERI POLA BILANGAN DI TINJAU DARI PERBEDAAN GENDER SISWA KELAS VIII SMP NEGERI 34 MAKASSAR - Aminah Nurfajri Al Saleh; Andi Husniati; Abdul Gaffar (Universitas Muhammadiyah Makassar, 2021)
Aminah Nurfajri Al Saleh. 2020. Difficulty Analysis of Solving Mathematical Problems with Number Patterns in terms of Gender Differences in Class VIII Students of SMP Negeri 34 Makassar. Essay. Mathematics Education Study Program, Teacher Training and Education Faculty, Muhammadiyah University of Makassar. Advisor I Andi Husniati and Advisor II Abdul Gaffar. This study aims to describe the location of the difficulties experienced by students in solving math problems on number pattern material for class VIII SMP Negeri 34 Makassar in the 2020/2021 school year in terms of gender differences. This research is a research that uses a qualitative descriptive approach which is designed to determine the location of the students' difficulties in solving math problems with the number pattern material in terms of gender differences. The data analyzed were data on the location of student difficulties in terms of gender differences. Data collection methods used were giving essay tests and interviews. The questions used in the test measure the location of the student's difficulty, amounting to 2 questions which contain indicators of the difficulty of concepts, principles, and verbal. These questions were done by 2 students in 45 minutes and the interview aimed to find out where the students' difficulties in answering the questions were. The results of the study provide information that there are differences in the difficulties of male and female students in solving math problems with the number pattern material. This is in line with the results of this study as it has been described that the difficulties of grade VIII students of SMP Negeri 34 Makassar include principle difficulties for male students while female students include principle and verbal difficulties.